Integrierte Multi-Sensor-Fusion für die simultane Lokalisierung und Kartenerstellung für mobile Robotersysteme - Emter, Thomas (Karlsruher Schriften zur Anthropomatik, 2021)
In this work, probabilistic methods for combining multiple sensors utilizing multi-sensor fusion for robust and precise localization and mapping in heterogeneous outdoor environments are presented. Aspects of increasing the reliability of landmark recognition are highlighted, as well as the integration of additional absolute and relative sensors using advanced filtering techniques.